Hubungan Antara Kontrol Diri Dan Konsep Diri Dengan Konformitas Teman Sebaya Pada Remaja Perempuan Pengguna Rokok Elektrik - I Made Risky Saputra; ⁠David Hizkia Tobing (Jurnal Ilmiah Wahana Pendidikan, 2026)
The use of electric cigarettes in female adolescents is now increasingly common and has the potential to cause various negative impacts, both from the physical and psychological health aspects. Based on preliminary studies conducted by the researcher, it was found that some female adolescents at Udayana University tend to be easily influenced by their peers in using electric cigarettes. It is assumed that there are protective factors that can minimize the negative impact of peers, namely self-control and self-concept. This study aims to determine the relationship between self-control and self-concept with peer conformity in female adolescent electric cigarette users at Udayana University. The type of research used was correlational quantitative research with accidental sampling technique involving 129 female adolescents as respondents. Data collection was conducted online through a questionnaire consisting of the Self-Control Scale, Self-Concept Scale, and Peer Conformity Scale. Data analysis used the Pearson correlation test. The results showed that there is a significant negative relationship between self-control and peer conformity (r = -0.345; p = 0.001), and also a significant negative relationship between self-concept and peer conformity (r = -0.374; p = 0.001). These findings indicate that the higher the self-control and self-concept, the lower the tendency of adolescents to follow the negative behavior of peer conformity in the use of electric cigarettes. Therefore, strengthening self-control and self-concept is important as an effort to prevent electric smoking behavior in female adolescents.